Serum Vascular Endothelial Growth Factor (VEGF) in DMPA Acceptors: Influence on Bleeding Occurrence - Pratiwi, Ratih; Amran, Rizani; Said, Usman; Saleh, Irsan (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To analyze the relationship between levels of serum vascular endothelial growth factor (VEGF) and bleeding occurrence in depo medroxyprogesterone acetate (DMPA) acceptors. Method: We employed a cross‐sectional study on 70 DMPA acceptors with DMPA use of 3 to 6 months who presented for midwifery service in Palembang. Blood samples were obtained in order to assess levels of serum VEGF using ELISA (enzyme‐linked immunoabsorbent assay) method. Laboratory assessments were carried out in PRODIA laboratory in Jakarta. Result: We recruited 70 subjects into our study. After 3 to 6 months of using DMPA, as much as 26 subjects (37.1%) reported complaints of bleeding and 44 subjects (62.9%) reported no bleeding. The mean level of serum VEGF in DMPA acceptors with bleeding was 355 K 170 pg/ml, and 323 K 202 pg/ml in acceptors with no bleeding. We identified a significant association between duration of use and bleeding occurrence (p0.05). Conclusion: In our sample, we found an association between duration of DMPA use and presence of bleeding but VEGF levels was not found to be different in women experiencing abnormal uterine bleeding and those who did not. Keywords: bleeding, DMPA acceptor, serum VEGF